Attributes of criminal justice systems: resources, performance and punitivity - Harrendorf, Stefan (International statistics on crime and justice, 2010)
This chapter focuses on attributes of the criminal justice system itself, namely on resources of the system, its performance and the systemic punitivity. Regarding resources, it focuses on police and prosecution personnel, professional judges and the staff in adult prisons. With respect to performance, quantitative productivity of the different criminal justice systems is analyzed, focusing on the rates of persons suspected per police officer, persons prosecuted per prosecutor, persons brought before a criminal court per prosecutor and persons convicted per prosecutor. Finally, systemic punitivity is estimated by the rate of total persons incarcerated per total persons convicted. The chapter covers data not only from the 10th UN-CTS, but also from earlier waves, back as late as to the 6th wave for trend analysis. As in the other chapters, the scale is worldwide. Trying to cover as many countries as possible, data for the analysis of the most recent status quo was not only taken from the 10th UN-CTS survey, but also from the 7th to 9th waves, with the year 2000 being the earliest “latest available” year covered here. For trend analysis, the preferred starting year was 1995, the first point in time in the 6th wave. If necessary, trend analysis was made for shorter periods of time instead.